Community Care in Reach: Mobilizing Harm Reduction and Addiction Treatment Services for Vulnerable Populations - Craig Regis; Jessie M. Gaeta; Sarah Mackin; Travis P. Baggett; Travis P. Baggett; Joan Quinlan; Elsie M. Taveras; Elsie M. Taveras (Frontiers Media S.A., 2020)
Opioid overdoses killed 47,600 people in the United States in 2017. Despite increasing availability of office-based addiction treatment programs, the prevalence of opioid overdose is historically high and disproportionately affects vulnerable populations, including people experiencing homelessness. Despite availability of effective treatment, many at greatest risk of death from overdose experience myriad barriers to care. Launched in 2018, the Community Care in Reach mobile health initiative uses a data-driven approach to bring harm reduction and medication for opioid use disorder directly to those at highest risk of near-term death. Proof-of-concept results suggest that mobile addiction services may serve as a model for expanding access to addiction care for the most vulnerable.